2022
DOI: 10.3390/molecules27020351
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent Drag Reduction with an Ultra-High-Molecular-Weight Water-Soluble Polymer in Slick-Water Hydrofracking

Abstract: Water-soluble polymers as drag reducers have been widely utilized in slick-water for fracturing shale oil and gas reservoirs. However, the low viscosity characteristics, high operating costs, and freshwater consumption of conventional friction reducers limit their practical use in deeper oil and gas reservoirs. Therefore, a high viscosity water-soluble friction reducer (HVFR), poly-(acrylamide-co-acrylic acid-co-2-acrylamido-2-methylpropanesulphonic acid), was synthesized via free radical polymerization in aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 38 publications
(64 reference statements)
0
27
0
Order By: Relevance
“…The six-membered heterocycle expanded the hydrodynamic volume of ASC, and the macromolecules were intertwined to form a threedimensional network structure, which made the ASC solution viscosity increase greatly with the increase of the mass fraction of thickener. 30 It indicated that ASC had good viscosity-increasing and thickening ability in high salinity brine and satisfied the requirements of continuous fluid preparation on the fracturing process. mass ratio of 5:1 with concentrations of 0, 5000, 10,000, 20,000, 50,000, 100,000, and 150,000 mg/L, respectively.…”
Section: Effect Of Asc Mass Fractionmentioning
confidence: 72%
See 2 more Smart Citations
“…The six-membered heterocycle expanded the hydrodynamic volume of ASC, and the macromolecules were intertwined to form a threedimensional network structure, which made the ASC solution viscosity increase greatly with the increase of the mass fraction of thickener. 30 It indicated that ASC had good viscosity-increasing and thickening ability in high salinity brine and satisfied the requirements of continuous fluid preparation on the fracturing process. mass ratio of 5:1 with concentrations of 0, 5000, 10,000, 20,000, 50,000, 100,000, and 150,000 mg/L, respectively.…”
Section: Effect Of Asc Mass Fractionmentioning
confidence: 72%
“…As the mass fraction of ASC increased, the hydrophilic groups on the molecular chain were ionized in the brine after the thickener diffused into brine, the higher thickener concentration, the more hydrophilic groups, which increasing the interaction force between the thickener and facilitating the diffusion of the thickener molecules into brine, so the dissolution rate was faster. The six‐membered heterocycle expanded the hydrodynamic volume of ASC, and the macromolecules were intertwined to form a three‐dimensional network structure, which made the ASC solution viscosity increase greatly with the increase of the mass fraction of thickener 30 . It indicated that ASC had good viscosity‐increasing and thickening ability in high salinity brine and satisfied the requirements of continuous fluid preparation on the fracturing process.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Additionally, they usually suffer from shear degradation under turbulent-flow conditions [ 28 ]. To overcome these shortcomings, researchers can enhance the temperature, salinity, and shear resistance of the polymer by introducing monomers with a ring structure, betaine, strong electrolyte group, and hydrophobic structure into the backbone of acrylamide [ 29 , 30 , 31 ]. Mao et al [ 29 ] reported a quaternary thickener P (acrylamide/acrylic acid/2-acrylamide-2-methylpropanesulfonic acid/hydrophobic monomer) and found that the thickener solution had a salt resistance of 30 × 10 4 mg/L and temperature resistance of 120 °C.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al [ 30 ] developed a terpolymer with acrylamide, acrylic acid, and 4-isopropenylcarbamoyl-benzene sulfonic acid with high temperature and shear resistance using the aqueous solution polymerization method; the viscosity of the fracturing fluid was about 135 mPa s after 120 min at 150 °C and it had a shear rate of 170 s −1 . Wei et al [ 31 ] synthesized a W/O emulsion thickener by using acrylamide, acrylic acid, acrylamide-2-methylpropanesulfonic acid, and dimethyldiallyl ammonium chloride and realized the continuous mixing of slick water fracturing fluids; the drag reduction rate of the thickener was greater than 70% at a salinity of 2.5 × 10 4 mg/L.…”
Section: Introductionmentioning
confidence: 99%